Ghost and the Machine: Bringing Untold Personal Spiritual and Cultural Experiences to Life Through the Medium of Digital Storytelling. - Ingrid Andersen; Elizabeth J Tisdell (Adult Education Research Conference, 2016)
This study examines learners’ perceptions of the experiences of transformation from the storytelling experience of digital stories within a graduate class on spirituality and culture, by means of the lenses of both transformative learning theory and storytelling theory.
Keywords: digital storytelling; transformative learning; storytelling theory; spirituality and culture